Priorización de los eventos peligrosos que ocasionarían daños en la Planta de Tratamiento de Agua Potable de Chaquishca de la ciudad de Guaranda, provincia Bolívar en el año 2021. - Naranjo Lombeida, Mayra Alejandra (2023)
Hazardous events affect people, property, the environment and sometimes disturb the continuity of basic services that human beings require to develop normally. Water is one of the vital elements that contribute to the progress of societies, therefore it is important to adapt risk reduction measures that help to safeguard the continuity, supply, treatment and distribution in a permanent and quality manner, both in normal situations and in emergency. This research work is focused on the prioritization of dangerous events that could cause damage in the Chaquishca drinking water treatment plant in the city of Guaranda, with the implementation of risk assessment tools that will allow us to achieve the objectives set, such as determining dangerous events that would cause damage to the treatment plant, evaluate the consequences of dangerous events and propose risk reduction actions. Matrices were generated for the prioritization of hazardous events Total Risk Evaluation System created by Engineer Paul Sanchez Franco, consists of the creation of evaluation parameters according to the magnitude/intensity, damage and return period variables, obtaining a risk level result. . Hazard Identification and Evaluation, considers different qualitative variables to be able to assess the seriousness to life, environment, property, speed of the event and the probability of reaching a risk result. In addition, a Gaussian dispersion modeling of the chlorine gas leak was carried out to visualize the affectation and what the event would be like if it were to happen. For the generation of the matrices, information was needed from the Chaquishca drinking water treatment plant and information from technical-scientific sources in charge of monitoring the different events that occur at the national level and for the elaboration of the modeling of the information of the area of storage, quantity of the substance and atmospheric data. Subsequently, a proposal is made to tend to reduce the risks of the significant risk that would affect the PTAPCH taking into account the source, means and person, helping to improve the capacities for decision-making and emergency care efficiently and quickly by part of the plant workers. Keywords: dangerous events, priority, level of risk